ACTIONAL CODE OF “ORPHAN WEDDING”: THE TRADITION OF PRIKAMYE IN RUSSIAN CONTEXT (Philological Studies, 2020)
The laments of an orphan bride is one of the markers of orphanhood as a special status in the traditional community. The article examines the ritual actions that accompanied the singing of such laments, as well as the loci and the objects which are used by participants. The research material includes archival data and publications of the 19th – 21st centuries. The Perm versions of the ceremony correlate with the traditions of other regions and detail the image of a Russian orphan wedding. The two most typical loci where orphan lamentations were performed are the home and the cemetery. In the house, the bride and assistants use the table, the periphery of the dwelling, and border loci. Sometimes orphan rituals included elements of theatricalization (searching for deceased parents, treating them, inviting a person-ritual substitute for the deceased). Border loci (hill, crossroads) were also selected outside the home and cemetery. A number of ritual gestures and objects (scarf, towel), which were used in an orphan's wedding, are known for the performances of funeral laments and are included in the common part of the “dictionary” of “lamentable” culture.
Keywords: wedding laments; orphan bride; orphan wedding; funeral laments; “lamentable” culture; Perm Region